Building National Character Through PKn Learning in Elementary School - Hasibuan, Shafira Fortuna (International Journal of Students Education, 2024)
Civic Education (PKN) is an important part of building national character. PKN is a national education system, in its implementation it can create, build, and develop abilities, as well as values contained in PKN learning. This means that education is able to facilitate students to carry out the learning process. PKN learning strategies need to be adjusted to the challenges of the times that continue to develop. This means that education is not a process that occurs by chance, but rather an effort that is planned and implemented with a specific purpose. This article discusses strategies and challenges in developing national character through PKN learning in elementary schools. Some effective strategies include the use of local value-based approaches, the application of active and collaborative learning, and the integration of technology in the learning process. The challenges faced include lack of resources, gaps between the curriculum and the actual needs of the community, and challenges in building a deep understanding of civic values amidst complex social dynamics. By paying attention to the right strategy and overcoming existing challenges, PKN subjects implemented in schools can be a foundation for building quality student character.